2005
DOI: 10.1146/annurev.biophys.34.040204.144500
|View full text |Cite
|
Sign up to set email alerts
|

Toroidal DNA Condensates: Unraveling the Fine Structure and the Role of Nucleation in Determining Size

Abstract: Toroidal DNA condensates have attracted the attention of biophysicists, biochemists, and polymer physicists for more than thirty years. In the biological community, the quest to understand DNA toroid formation has been motivated by its relevance to gene packing in certain viruses and by the potential use of DNA toroids in artificial gene delivery (e.g., gene therapy). In the physical sciences, DNA toroids are appreciated as a superb model system for studying particle formation by the collapse of a semiflexible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

16
258
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(274 citation statements)
references
References 86 publications
16
258
0
Order By: Relevance
“…The non-linearity in this latter case is clearly present and is captured in a single parameter describing the onset of DNA kink formation. This clearly exhibited elastic nonlinearity is taken as the motivation for the present study that attempts to derive the macroscopic consequences of this interesting microscopic elastic behavior of DNA.Another interesting facet of DNA behavior is that under specific solution conditions, it condenses into highly compact structures with pronounced symmetry [8][9][10][11]. This condensation phenomenon serves as an example of high polymer density packing in biology and of polymer phase transitions and phase separations in general, being relevant also for artificial gene delivery [12,13].…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…The non-linearity in this latter case is clearly present and is captured in a single parameter describing the onset of DNA kink formation. This clearly exhibited elastic nonlinearity is taken as the motivation for the present study that attempts to derive the macroscopic consequences of this interesting microscopic elastic behavior of DNA.Another interesting facet of DNA behavior is that under specific solution conditions, it condenses into highly compact structures with pronounced symmetry [8][9][10][11]. This condensation phenomenon serves as an example of high polymer density packing in biology and of polymer phase transitions and phase separations in general, being relevant also for artificial gene delivery [12,13].…”
mentioning
confidence: 94%
“…Another interesting facet of DNA behavior is that under specific solution conditions, it condenses into highly compact structures with pronounced symmetry [8][9][10][11]. This condensation phenomenon serves as an example of high polymer density packing in biology and of polymer phase transitions and phase separations in general, being relevant also for artificial gene delivery [12,13].…”
mentioning
confidence: 99%
“…On the molecular level, the torus shape is preferred by numerous biological and chemical macromolecules, such as DNA condensates [4], proteins [5] and oligosaccharides [6], to name just a few. Toroidal symmetries are also encountered frequently in solid-state systems including carbon nanotubes [7] and ferroelectrics [8,9].…”
mentioning
confidence: 99%
“…[1][2][3][4][5] Polyelectrolyte theory has figured out that the attractive potential that leads to DNA compaction originates from correlated fluctuation of counterions shared between DNA segments. 6 Experimental observations have revealed that DNA condensates have generally a toroidal geometry with a typical size of ∌100 nm in diameter.…”
mentioning
confidence: 99%